1995
DOI: 10.1002/qua.560540110
|View full text |Cite
|
Sign up to set email alerts
|

Large basis sets and geometry optimizations in embedded cluster calculations

Abstract: mIn the embedded cluster method, a cluster is embedded in a correction potential. This potential adds the long-range electrostatic forces of the crystal and subtracts the electrostatic potential of the boundary errors of the cluster. The correction potential is calculated from the wave function of the cluster and the crystal. So far, the method has only been used on a cluster having the same geometry and basis set as that of the crystal. Here, we calculated the adsorption energies of NH3 and NH: on an embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…One relevant effect is the influence of the long-range electrostatic field due to the density of charge belonging to the atoms surrounding the active site. The importance of such effect has been very recently studied by Greatbanks et al , and Teunissen et al., , who have shown, by means of an embedded cluster technique, that in the case of NH 3 adsorbed in both H-ZSM5 and chabazite the long-range electrostatic field increases the binding energies with respect to those computed for the bare clusters. Furthermore, the Coulombic field also increases the stability of the charged complex (in which NH 4 + is formed) with respect to the neutral H-bonded complex.…”
Section: Resultsmentioning
confidence: 99%
“…One relevant effect is the influence of the long-range electrostatic field due to the density of charge belonging to the atoms surrounding the active site. The importance of such effect has been very recently studied by Greatbanks et al , and Teunissen et al., , who have shown, by means of an embedded cluster technique, that in the case of NH 3 adsorbed in both H-ZSM5 and chabazite the long-range electrostatic field increases the binding energies with respect to those computed for the bare clusters. Furthermore, the Coulombic field also increases the stability of the charged complex (in which NH 4 + is formed) with respect to the neutral H-bonded complex.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a quantum chemical calculation should also be consistent from a quantum chemical point of view and requires a correct model to represent the zeolite. [3][4][5][6][7][8][9][10] Concerning the quantum chemical method, we find that a relatively large basis set should be used. It is also important to apply the counterpoise correction (CPC) to correct for the basis set superposition error (BSSE).1112 Furthermore, it is important to include electron correlation.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the modern computational chemistry is a promising alternative for the study of catalytic systems. Recently, it has been demonstrated that the embedded cluster approach produces valuable information for the host–guest interaction in the catalytic processes 3–11. In fact, the proposed QM/MM (quantum mechanics/molecular mechanics) techniques represent the state‐of‐the‐art, together with ab initio MD (molecular dynamics), to study chemical processes involving small guest molecules in host zeolite systems.…”
Section: Introductionmentioning
confidence: 99%
“…It deals with single clusters demanding smaller amount of computer time and memory than those required for periodic boundary conditions calculations. Also this approach takes into account long‐range electrostatic forces and boundary effects, giving adsorption energies with an uncertainty of just a few kJ/mol 3, 4. Moreover, this type of model allows for study of the role of the chemical composition of the catalyst on the catalytic process performance.…”
Section: Introductionmentioning
confidence: 99%